Aktivitas Antioksidan dan Profil Senyawa Bioaktif Rumput Laut Sargassum sp. - Jihan Novitasari; Abd. Rohim; Maylina Ilhami Khurniyati; Pinctada Putri Pamungkas; Elsa Yuliana (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2025)
Indonesia as a maritime country has abundant marine biological resources, including brown algae Sargassum sp. This study aims to explore the antioxidant capacity and characteristics of bioactive compounds from methanol extract of brown algae Sargassum sp. taken from Kondang Merak Beach, Malang Regency. The maceration method was chosen for the extraction process using various times (20, 40, and 60 minutes) and the ratio of seaweed powder to solvent (1:10, 1:20, and 1:30 g/ml). Antioxidant activity was analyzed using the DPPH method, while total phenolic and flavonoid contents were determined using the Folin–Ciocalteu method and spectrophotometry. Identification of bioactive compounds of Sargassum sp. was tested using Liquid Chromatography–High Resolution Mass Spectrometry (LC-HRMS), which allows more accurate and comprehensive detection of compounds. The results revealed that treatment with a time of 60 minutes and a solvent ratio of 1:30 produced the best antioxidant capacity with an IC₅₀ value of 4.71 mg/ml, a total phenolic content of 1.31 mg GAE/g, and a total flavonoid content of 8.80 mg QE/g. LC-HRMS analysis revealed various bioactive compounds including unsaturated fatty acids, flavonoids, terpenoids, and carotenoids, such as α-eleostearic acid, eicosapentaenoic acid, tangeritin, nobiletin, curcumin, and astaxanthin. The presence of these compounds plays an important role in explaining the high antioxidant capacity of Sargassum sp. extract. Therefore, brown algae Sargassum sp. has potential as a natural source of antioxidant compounds for functional food, pharmaceutical, and cosmetic applications.